When Religious Faith Mutilates Gender Equality: Women Entry in Sabarimala Temple in Kerala. Issue 2 (December 2019) - Bijukumar, V.
The brewing controversy over allowing entry of women of all age groups into the hill shrine of Ayyappa in Kerala polarized public opinion on women's equal access to sacred spaces and the perpetuation of tradition in places of worship. Protagonists of gender equality claim that the restriction is as an attack on women's right to access sacred places and a violation of Article 14 (right to equality) and Article 25(2) of the Indian Constitution which guarantees the right to religious freedom to all, thereby allowing irrationality to creep into the most literate society in the country. Critics protesting against the entry argue that it is against the centuries-old-practices-defined customs. According to them, women's entry would pollute the temple and the celibate nature of Ayyappa should be protected.